SEARCH FOR SCALAR LEPTOQUARKS FROM Z(0) DECAYS - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Anassontzis, E; Antilogus, P; et al. (1992)
We have searched for pair produced scalar leptoquarks each decaying to a quark and a charged lepton in a sample of 116 000 hadronic Z0 events produced at LEP. No candidate was detected and cross section and branching ratio limits are set for the above process at 95% CL. Mass limits are found to be about 42 GeV/c2 depending only slightly on the models used and a coupling times branching ratio exclusion line is drawn for a scalar leptoquark with a free coupling. We have also probed the mass region above 45 GeV/c2 for a singly produced scalar leptoquark and set limits on the cross section and the coupling λ2/4π up to 60 GeV.